2017
DOI: 10.1038/aps.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits ox-LDL-induced inflammation in human endothelial cells in vitro by inhibiting the mTORC2/PKC/c-Fos pathway

Abstract: Rapamycin and its derivative possess anti-atherosclerosis activity, but its effects on adhesion molecule expression and macrophage adhesion to endothelial cells during atherosclerosis remain unclear. In this study we explored the effects of rapamycin on ox-LDL-induced adhesion molecule expression and macrophage adhesion to endothelial cells in vitro and the underlying mechanisms. Ox-LDL (6-48 μg/mL) dose-dependently increased the protein levels of two adhesion molecules, intercellular adhesion molecule-1 (ICAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Intercellular adhesion molecule‐1 (ICAM‐1) and E‐selection are both common adhesion molecules that play important roles in inflammation. The LDL inflammation mechanism may interact with the environment as a carcinogen in lung cancer formation 34 . Other reports have shown that lipid accumulation and expression of CXCL16 and Nephrin are induced by oxidized LDL 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular adhesion molecule‐1 (ICAM‐1) and E‐selection are both common adhesion molecules that play important roles in inflammation. The LDL inflammation mechanism may interact with the environment as a carcinogen in lung cancer formation 34 . Other reports have shown that lipid accumulation and expression of CXCL16 and Nephrin are induced by oxidized LDL 35 .…”
Section: Discussionmentioning
confidence: 99%
“…(Hansson et al, 2015) Here we induced endothelial cell inflammation by challenging HUVECs with ox-LDL according to literature. (Sun et al, 2018) and then treated cells with LEO. LEO at a concentration of 50μM or less did not influence cell viability and showed no toxicity.…”
Section: Leo Increased Enos Expression No Production But Inhibited mentioning
confidence: 99%
“…RAPA has been found to attenuate monocyte chemotactic protein-1 expression in the aortic arch of apoE-deficient mice fed an atherogenic diet, a finding that illustrates that RAPA has anti-migratory effects on macrophages (Castro et al, 2004). Additionally, RAPA can dose-dependently decrease the ox-LDL-induced expression of ICAM-1 and E-selectin and inhibit the adhesion of monocytes to human umbilical vein-endothelial cells through suppressing the activation of MTORC2, and then inhibiting PKC phosphorylation and c-fos expression (Sun et al, 2017). Moreover, TNF-α, an inflammatory cytokine, can drive adhesion molecule expression through activating the Raf-1-Merk1/2-ERK1/2 pathway (Roberts and Der, 2007).…”
Section: Anti-atherosclerotic Effects Of Rapamycinmentioning
confidence: 99%